Development and validation of a military fear avoidance questionnaire - Cooper, Carly; Frey, Bruce; Day, Charles (Frontiers in Rehabilitation Sciences, 2022)
Chronic pain due musculoskeletal injury is the leading cause of disability and reduced combat readiness in the U.S. Army. Unidimensional pain management systems are not effective in addressing the complex phenomenon of pain-related disability. Growing evidence has supported use of the Fear Avoidance Model as a suitable model to address pain-related disability and chronicity from a multidimensional pain neuroscience approach. While several fear avoidance measurement tools exist, one that addresses the complexity of the Army environment encouraged the authors to develop and test the reliability and validity of a military specific questionnaire. This study developed and validated an Army specific fear avoidance screening, the Return to Duty Readiness Questionnaire (RDRQ), which subsequently demonstrated good psychometric properties. Reliability coefficients demonstrate high internal consistency values both during pilot study (α = 0.96) and validation study (α = 0.94, ωt = 0.94). A Correlation Coefficient of 0.74 when compared with the Fear Avoidance Components Scale (FACS) suggests good concurrent validity. Future study should include replication in a new army population, investigation of responsiveness, test-retest reliability, structural validity and establishing severity scores with minimal clinically important differences to enhance utility.